Carcinoembryonic Antigen (CEA)-Specific 4-1BB-Costimulation Induced by CEA-Targeted 4-1BB-Agonistic Trimerbodies - Mikkelsen, Kasper; Harwood, Seandean Lykke; Compte, Marta; Merino, Nekane; Mølgaard, Kasper; Lykkemark, Simon; Alvarez-Mendez, Ana; Blanco, Francisco J.; Álvarez-Vallina, Luis (Frontiers in Immunology, 2019)
4-1BB (CD137) is an inducible costimulatory receptor that promotes expansion and survival of activated T cells; and IgG-based 4-1BB-agonistic monoclonal antibodies exhibited potent antitumor activity in clinical trials. However, the clinical development of those antibodies is restricted by major off-tumor toxicities associated with FcγR interactions. We have recently generated an EGFR-targeted 4-1BB-agonistic trimerbody that demonstrated strong antitumor activity and did not induce systemic inflammatory cytokine secretion and hepatotoxicity associated with first-generation 4-1BB agonists. Here, we generate a bispecific 4-1BB-agonistic trimerbody targeting the carcinoembryonic antigen (CEA) that is highly expressed in cancers of diverse origins, especially carcinomas. The CEA-targeted anti-4-1BB-agonistic trimerbody consists of three 4-1BB-specific single-chain fragment variable antibodies and three anti-CEA single-domain antibodies positioned around a murine collagen XVIII-derived homotrimerization domain. The trimerbody was produced as a homogenous, non-aggregating, soluble protein purifiable by standard affinity chromatographic methods. The purified trimerbody was found to be trimeric in solution, very efficient at recognizing 4-1BB and CEA, and potently costimulating T cells in vitro in the presence of CEA. Therefore, trimerbody-based tumor-targeted 4-1BB costimulation is a broadly applicable and clinically feasible approach to enhance the costimulatory environment of disseminated tumor lesions.